Transformasi Digital Sebagai Strategi Peningkatan Daya Saing Industri Ekspor Ditengah Perubahan Nilai Tukar dan Suku Bunga: Penelitian - Flowrensari Haggata Br Ginting; Saskia Bella; M Yudi Fajri; Bunga Madu Simanungkalit; Khairani Alawiyah Matondang (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
International trade today is no longer solely influenced by classical factors such as product quality and production costs, but also by global macroeconomic dynamics, particularly exchange rate fluctuations and interest rate changes. Indonesia’s export industry is highly vulnerable to these uncertainties, which requires sustainable strategies to maintain competitiveness. This study aims to answer the main research question: how can digital transformation serve as an effective strategy to strengthen the competitiveness of Indonesia’s export industry amid exchange rate volatility and interest rate fluctuations? The research employs a qualitative descriptive approach through a literature review, analyzing academic journals, reports from international financial institutions, and government publications. The findings reveal that digital transformation provides multiple advantages, including production efficiency, wider market access through digital platforms, improved supply chain transparency, and access to alternative non-conventional financing. These results highlight that digitalization is not merely a short-term solution, but rather a fundamental strategy to build sustainable competitiveness and adaptability for Indonesia’s export sector in the face of global economic uncertainty.